Semiconductor surfaces structurization induced by ultrasound - Savkina, R.K. (Functional Materials, 2012)
Gallium arsenide and silicon substrates were exposed to cavitation impact induced by focusing a high frequency acoustic wave into liquid nitrogen. Optical and atomic force microscopy methods as well as energy dispersive X-ray spectroscopy were used for analysis of the surface morphology and chemical composition of semiconductor surface. Microstructures formation as well as change of the chemical composition of the surface was found. The morphology of the structures is highly dependent on the acoustic parameters. Зразки арсеніду галію і кремнію піддано впливу кавітації, збудженої у кріогенній рідині сфокусованим високочастотним ультразвуком. Морфологія поверхні оброблених зразків вивчалася методом оптичної та атомної силової мікроскопії, а також методом електронної мікроскопії з елементним аналізом. Виявлено утворення субмікронних структур і зміну хімічного складу поверхні. Морфологія структур залежить від акустичних параметрів. Образцы арсенида галлия и кремния подвергнуты воздействию кавитации, возбужденной в криогенной жидкости сфокусированным высокочастотным ультразвуком. Морфология поверхности обработанных образцов изучалась методом оптической и атомной силовой микроскопии, а также методом электронной микроскопии с элементным анализом. Обнаружено образование субмикронных структур и изменение химического состава поверхности. Морфология структур зависит от акустических параметров.